(untitled) - Hejhalova, Bozena (Doprava a spoje, 2012)
The article analyzes the new legal framework for sea freight which is defined by the UN Convention on Contracts for the International Carriage of Cargo (wholly or partly) by sea, also known as ``Rotterdam Rules''. The article also points out the inconsistency in the legal conditions for transport of the carriage of cargo by sea because of the existence of three international conventions. (International Convention for the Unification of Certain Rules of Law relating to Bills of Lading, Convention on the Maritime transport, Convetion on Contracts for the International Carriage of Cargo).